Exchange rate economics - Isard, Peter; Cambridge University Press (Cambridge [England] ; New York : Cambridge University Press, 1995)
This book describes and evaluates the literature on exchange rate economics. It provides a wide-ranging survey, with background on the history of international monetary regimes and the institutional characteristics of foreign exchange markets, an overview of the development of conceptual and empirical models of exchange rate behavior, and perspectives on the key issues that policymakers confront in deciding whether, and how, to try to stabilize exchange rates. The treatment of most topics is reasonably compact, with extensive references to the literature for those desiring to pursue individual topics further. The level of exposition is relatively easy to comprehend; the historical and institutional material (part I) and the discussion of policy issues (part III) contain no equations or technical notation, while the chapters on models of exchange rate behavior (part II) are written at a level intelligible to first-year graduate students or advanced undergraduates.
The book will enlighten both students and policymakers, and should also serve as a valuable reference for many research economists.
-- 1. Introduction -- 2. Foreign exchange markets and the marketability of money -- 3. Exchange rate arrangements and international monetary regimes -- 4. Exchange rates and national price levels -- 5. Exchange rates and interest rates -- 6. Exchange rates and the balance of payments -- 7. News, revisions in expectations, and exchange rate dynamics -- 8. Empirical estimates of structural exchange rate models -- 9. New perspectives from optimizing models of realignments under fixed exchange rates -- 10. New directions for conceptual models of flexible exchange rates -- 11. The choice of exchange rate arrangements -- 12. Policy-oriented perspectives on exchange rate stability.
Includes bibliographical references (pages 237-266) and indexes.
Keywords: Foreign exchange rates; Foreign exchange rates -- Econometric models